2014
DOI: 10.1038/srep04293
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism studies on the interactions of antimicrobial peptides with bacterial cells

Abstract: Studying how antimicrobial peptides interact with bacterial cells is pivotal to understand their mechanism of action. In this paper we explored the use of Circular Dichroism to detect the secondary structure of two antimicrobial peptides, magainin 2 and cecropin A, with E. coli bacterial cells. The results of our studies allow us to gain two important information in the context of antimicrobial peptides- bacterial cells interactions: peptides fold mainly due to interaction with LPS, which is the main component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 34 publications
3
104
1
Order By: Relevance
“…It is acknowledged that most ␣-helical AMPs are unstructured in aqueous solution and adopt an ␣-helical conformation upon interaction with the bacterial membrane (40). Although unstructured in pure water, LL-37 was reported to be ␣-helical in most physiological buffers and in solutions containing the ion compositions of biological fluids (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is acknowledged that most ␣-helical AMPs are unstructured in aqueous solution and adopt an ␣-helical conformation upon interaction with the bacterial membrane (40). Although unstructured in pure water, LL-37 was reported to be ␣-helical in most physiological buffers and in solutions containing the ion compositions of biological fluids (39).…”
Section: Discussionmentioning
confidence: 99%
“…S2 in the supplemental material) (34)(35)(36)(37)(38). Circular dichroism (CD) showed that both AMPs are unstructured in water, although they adopt an ␣-helical conformation in the presence of the organic solvent 2,2,2-trifluoroethanol (TFE) or upon interaction with membrane phospholipids (35,39,40). The conformation of cathelicidins in host physiological fluids remains unclear, since these fluids are incompatible with CD experiments.…”
mentioning
confidence: 96%
“…We measured changes in circular dichroism of the Mig1 fusion construct upon addition of PEG (Figure 1(k)) in a wavelength range known to be sensitive to transitions between ordered and intrinsically disordered states [71,72]. We also noted similar levels of disorder content in the Msn2 protein far from the Zn finger motif.…”
Section: Resultsmentioning
confidence: 71%
“…[6] have been reported to exert strong anticancer effect against various types of cancers such as breast, prostrate, ovarian and skin cancers [7]. Considering the immense amount of AMP sequences deciphered till date [8] such peptide based drugs can prove out to be vital novel anticancer pharmaceuticals with minimal side effects.…”
Section: Introductionmentioning
confidence: 99%